Hydrodynamic flow between rotating eccentric cylinders with suction at the porous walls - S. Meena; P. Kandaswamy; Lokenath Debnath (International Journal of Mathematics and Mathematical Sciences)
The flow of a viscous, incompressible fluid between two eccentric rotating porous cylinders with suction/injection at both the cylinders, for very small clearance ratio is studied. The expressions for various flow characteristics are obtained using perturbation analysis. Streamlines and pressure plots are shown graphically for various values of flow parameters and discussed.